Analisis Visualisasi Film Menjelang Magrib Mengenai Tradisi Pasung Pada Orang Dalam Gangguan Jiwa Menggunakan Teori Semiotika - Rahmat Ramadhan; Jupriani Jupriani (Jurnal Mahasiswa Kreatif, 2023)
The purpose of this research is to analyze the visual signs in Menjelang Magrib film regarding the tradition of pasung on people with mental disorders using Charles Sanders Pierce theory. The type of research used is descriptive qualitative with content analysis method to analyze the visuals and identify the meanings that appear in the film. This research uses Charles Sanders Pierce's semiotic theory through aspects of icons, symbols, and indexes that focus on the tradition of pasung on people with mental disorders experienced by Nina. The object of this research is the movie "Menjelang Magrib". The results of this study indicate that the tradition of pasung carried out on people with mental disorders has a negative impact, because it will hurt mentally and physically the person who is shackled. The tradition of pasung experienced by Nina is a social campaign message to reject the practice of pasung tradition as a form of human rights struggle where people with mental disorders should be treated better.